2020
DOI: 10.1177/1947603520904757
|View full text |Cite
|
Sign up to set email alerts
|

Particulated Cartilage for Chondral and Osteochondral Repair: A Review

Abstract: Introduction Injuries to articular cartilage have a poor spontaneous repair potential and no gold standard treatment exist. Particulated cartilage, both auto- and allograft, is a promising new treatment method that circumvents the high cost of scaffold- and cell-based treatments. Materials and Methods A comprehensive database search on particulated cartilage was performed. Results Fourteen animal studies have found particulated cartilage to be an effective treatment for cartilage injuries. Many studies suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 54 publications
0
36
0
2
Order By: Relevance
“…Clinical experience was still limited, with short-term studies demonstrating the procedure to be safe, feasible, and effective, including improvements in subjective patient scores and MRI evidence of good defect fill, but a randomized trial and long-term follow-up are lacking. 6…”
Section: Discussionmentioning
confidence: 99%
“…Clinical experience was still limited, with short-term studies demonstrating the procedure to be safe, feasible, and effective, including improvements in subjective patient scores and MRI evidence of good defect fill, but a randomized trial and long-term follow-up are lacking. 6…”
Section: Discussionmentioning
confidence: 99%
“…So far, about 10,000 people have received PJAC surgery worldwide, and the long-term clinical effects of PJAC surgery have been confirmed. 10,13,15,16,17,29,37 In 2013, Tompkins et al 37 applied the PJAC technique to treat 16 patients with patellar cartilage disease. After 28 months, the patients’ International Knee Documentation Committee (IKDC) scores had improved significantly, and 89% and 73% of the patients’ MRI results showed normal or near-normal cartilage repair, respectively, at the repaired defect area.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been found that the long-term treatment efficacy of microfractures is not good, and the proliferative capacity of PJAC is stronger than that of adult cells, which creates a promising treatment plan. 10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the characteristics of strong proliferation of transplanted juvenile cartilage, particulated juvenile allograft cartilage (PJAC) from donors under 13 years old is prepared and stored at low temperature, and then applied with brin glue to the cartilage defects [9]. At present, DeNovo NT, a commercial product of PJAC, has been widely used in clinical practice and has achieved satisfactory therapeutic effects [10][11][12][13][14][15]. Compared with microfractures and ACC, PJAC transplantation has better long-term e cacy.…”
Section: Introductionmentioning
confidence: 99%